RNA-Containing Immune Complexes Formed by Anti-Melanoma Differentiation Associated Gene 5 Autoantibody Are Potent Inducers of IFN-α - Wang, Kaiwen; Zhao, Jiangfeng; Wu, Wanlong; Xu, Wenwen; Sun, Shuhui; Chen, Zhiwei; Fu, Yakai; Guo, Li; Du, Hui; Ye, Shuang (Frontiers in Immunology, 2021)
Objective Anti-melanoma differentiation-associated gene 5 (MDA5) autoantibody is a distinctive serology hallmark of dermatomyositis (DM). As an autoantigen, MDA5 is a cytoplasmic RNA recognition receptor. The aim of this study was to address the question of whether the RNA-containing immune complex (IC) formed by MDA5 and anti-MDA5 could activate type I interferon (IFN) response. Method Patients with anti-MDA5+ DM (n = 217), anti-MDA5− DM (n = 68), anti-synthase syndrome (ASyS, n = 57), systemic lupus erythematosus (SLE, n = 245), rheumatoid arthritis (RA, n = 89), and systemic sclerosis (SSc, n = 30) and healthy donors (HD, n = 94) were enrolled in our studies. Anti-MDA5 antibody was detected by line blotting, enzyme-linked immunosorbent assay (ELISA), immunoprecipitation, and Western blotting. Cytokine profiling was determined by multiplex flow cytometry, and IFN-α was further measured by ELISA. Type I IFN-inducible genes were detected by quantitative PCR (qPCR). RNA–IC binding was analyzed by RNA immunoprecipitation. Plasmacytoid dendritic cells (pDCs) derived from healthy donors were cultivated and stimulated with MDA5 ICs with or without RNase and Toll-like receptor 7 (TLR-7) agonist. The interaction between MDA5 ICs and TLR7 was evaluated by immunoprecipitation and confocal microscopy. Results According to our in-house ELISA, the presence of anti-MDA5 antibody in 76.1% of DM patients, along with 14.3% of SLE patients who had a lower titer yet positive anti-MDA5 antibody, was related to the high level of peripheral IFN-α. ICs formed by MDA5 and anti-MDA5 were potent inducers of IFN-α via TLR-7 in an RNA-dependent manner in vitro. Conclusion Our data provided evidence of the mechanistic relevance between the anti-MDA5 antibody and type I IFN pathway.